Recent Developments in the Remote Radio Control of Insect Flight - Sato, Hirotaka; Maharbiz, Michel M. (Frontiers in Neuroscience, 2010)
The continuing miniaturization of digital circuits and the development of low power radio systems coupled with continuing studies into the neurophysiology and dynamics of insect flight are enabling a new class of implantable interfaces capable of controlling insects in free flight for extended periods. We provide context for these developments, review the state-of-the-art and discuss future directions in this field.